2022
DOI: 10.1111/acel.13572
|View full text |Cite
|
Sign up to set email alerts
|

Ipriflavone as a non‐steroidal glucocorticoid receptor antagonist ameliorates diabetic cognitive impairment in mice

Abstract: Diabetic cognitive impairment (DCI) is a common diabetic complication with hallmarks of loss of learning ability and disorders of memory and behavior. Glucocorticoid receptor (GR) dysfunction is a main reason for neuronal impairment in brain of diabetic patients. Here, we determined that ipriflavone (IP) a clinical anti-osteoporosis drug functioned as a non-steroidal GR antagonist and efficiently ameliorated learning and memory dysfunction in both type 1 and 2 diabetic mice. The underlying mechanism has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Thus, synaptic functions can be protected, and learning and memory ability can be improved by inhibiting P-Tau. 47 The current study showed that the level of phosphorylated Tau inhibited by THSWD intervention, indicating that THSWD can also participate in DACD treatment by reducing the Tau phosphorylation. However, both Aβ and P-Tau production can be affected by the AGEs-RAGE pathway.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, synaptic functions can be protected, and learning and memory ability can be improved by inhibiting P-Tau. 47 The current study showed that the level of phosphorylated Tau inhibited by THSWD intervention, indicating that THSWD can also participate in DACD treatment by reducing the Tau phosphorylation. However, both Aβ and P-Tau production can be affected by the AGEs-RAGE pathway.…”
Section: Discussionsupporting
confidence: 51%
“…Type 1 diabetes (T1DM) was induced as described previously [ 30 , 31 ]. Briefly, 7-week-old C57BL/6J mice were injected intraperitoneally with a single dose of STZ (150 mg/kg, Sigma-Aldrich) that was freshly dissolved in pH 4.5 citrate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…A raise in phosphorylation of NF-κB p65 and IκBα is detected in the hippocampus from diabetic mice after STZ administration [63,97] and higher NF-κB immunostaining is also detected in the hypothalamus, basolateral amygdala and cortex from diabetic mice [90]. Later studies have supported these observations showing that altered signaling in the hippocampus from diabetic mice includes increased protein expression of HMGB1/TLR4/NF-κB pathway, NLRP3 inflammasome [97] and the glucocorticoid receptor/ NF-κB/NLRP3/apoptosis-associated speck-like protein (ASC)/caspase-1 pathway [100].…”
Section: Streptozotocin (Stz)-induced Diabetic Micementioning
confidence: 86%